Professor Pavlo F. Tushkan (Tushkanov) (1867–1942): life gives agricultural science and education of Ukraine - V. A. Vergunov (History of science and technology, 2018)
The researcher comprehensively revealed the life fate and creative achievements of Pavlo F. Tushkan (Tushkanov) (1867–1942) for the first time. He completely analyzed scientist’s achieve-ments in the field of formation and development of agricultural science and education in Ukraine. During 1894-1899 and 1927-1934 Poltava occupied a special place among them.In the first period, he is an assistant to the director of the Poltava experimental field and the secretary of the Poltava Society of Agriculture, and in the second, he is a professor and founder, the first head of the De-partment of Agriculture of the Poltava Agricultural Institute. The author proved the decisive role of the scientist in the organization of agricultural education during the Ukrainian Revolution (1917–1919) and agricultural experimental work through the Agricultural Scientific Committee of Ukraine (1921–1927) and the Ukrainian Academy of Agricultural Sciences (1934–1936). In addition, the researcher pronounced Pavlo F. Tushkan’s social and political activity in the field of archeology.